Evaluation of Erzurum City Center within the Scope of Blue-Green Infrastructure - Demircan, Neslihan; Aksu, Ayşegül; Kuzulugil, Ali Can (Bartın Üniversitesi, 2020)
Urbanization is increasing day by day. About two thirds of people live in cities. Increasing urbanization creates great pressures on both natural and cultural landscape resources in urban areas. Accurate and effective planning within the scope of blue-green infrastructure will reduce global pressures to solve these problems. The blue-green infrastructure is effective in achieving this goal with its versatility and connectivity. In the study, blue-green infrastructure studies in the world and Turkey were examined. Blue-green infrastructure components in Erzurum were evaluated. In the city where the current active green areas per capita (86.43 ha) are 2.28 m², it is seen that the urban green areas are insufficient as one of the blue-green infrastructure components. In addition, the insufficiency of other components was determined in Erzurum city. For this reason, suggestions have been made to increase the blue-green infrastructure components.

Kentleşme gün geçtikçe artmaktadır. İnsanların yaklaşık üçte ikisi kentlerde yaşamaktadır. Kentleşmenin artması, kentsel alanlarda hem doğal hem de kültürel peyzaj kaynaklarına büyük baskılar oluşturmaktadır. Bu sorunların çözülmesi için mavi -yeşil altyapı kapsamında yapılacak doğru ve etkili planlamalar, küresel baskıları azaltamayı sağlayacaktır. Mavi-yeşil alt yapı çok yönlü olması ve bağlantılığı sağlamasıyla bu hedefin başarılmasında etkindir. Çalışmada, mavi- yeşil altyapı sistemleri hakkında dünya ve Türkiye'de yapılan çalışmalar incelenmiştir. Erzurum'daki Mavi-yeşil altyapı bileşenleri değerlendirilmiştir. Kişi başına düşen mevcut aktif yeşil alanların (86,43 ha) 2,28 m² olduğu kentte mavi-yeşil altyapı bileşenlerinden, kentsel yeşil alanların yetersiz olduğu sayısal olarak görülmektedir. Ayrıca Erzurum kentinde diğer bileşenlerin de yetersizliği belirlenmiştir. Bu sebeple mavi-yeşil altyapı bileşenlerini artırmaya yönelik önerilerde bulunulmuştur.
Mavi-Yeşil Altyapı Kapsamında Erzurum Kent Merkezinin Değerlendirilmesi
Keywords: Environmentally Sustainable Engineering; Çevresel Olarak Sürdürülebilir Mühendislik